Extended Synchronous Variational Integrators for Wave Propagations on Non-Uniform Meshes (Communications in Computational Physics, 2020)
This paper is concerned with the classical problem of wave propagation indiscrete models of nonuniform resolution. We extend the traditional asynchronousvariational integrators (AVIs) method to higher order and couple different spatial elements to adapt to nonuniform meshes. We show that the extension of AVIs methodis stable, convergent and may reduce the spurious inter-grid reflection across mesheswith different sizes. Numerical experiments are provided to verify the stability andconvergence of the extended AVIs. The total energy is numerically conserved in ourexperiments.
Keywords: Asynchronous variational integrators; nonuniform mesh; local time stepping; spurious reflections.